Redevelopment after the Abruzzo event - Margherita Mori (European Regional Science Association (ERSA), 2011)
Natural disasters raise quite a number of interdisciplinary issues concerning regional economic growth and local development, as well as public finance and sustainability, to mention only a few of them. These issues deserve special attention in our globalized world, given the expectation of a growing impact of climate-related disasters: no surprise that disaster management stands as a new discipline aimed at bridging the gap between theory and practice, so as to prevent natural disasters in the first place; afterwards, considerable efforts are required to accelerate business recovery, quickly restore vital energies, and hopefully carry out specific improvement projects as a sort of compensation for the (both personal and economic) losses suffered. Interesting lessons can be learned from natural disasters and can be shared as a payback to those who helped upon their occurrence. Actually, cooperation calls for cross-cultural activities that are likely to benefit from direct experience made by impacted scholars and practitioners: a case in point has to do with the earthquake that devastated L'Aquila and its environs on April 6, 2009 causing more than 300 deaths, apart from extensive damage in the Abruzzo region, in Central Italy; the Abruzzo event - as this natural disaster is currently referred to - fuels the debate on redevelopment problems to be faced under similar circumstances, that may obliterate the economic environment and attractiveness of an area in a few moments. Due to the huge amount of money needed to undertake appropriate strategies, finance plays a key role and useful insights can be gained by exploring the process of financial innovation. A supporting argument deals with the recourse to micro-finance in order to make the business and economic scenario revive after a natural disaster: micro-credit might be resorted to even within the framework of new financial engineering instruments, such as Urban Development Funds, recently promoted by the European Investment Bank; they include JESSICA (Joint European Support for Sustainable Investment in City Areas) and JEREMIE (Joint European Resources for Micro to Medium Enterprises), to be properly considered as strategic tools in sight of redeveloping L'Aquila and its surrounding boroughs.
Keywords: 330